2014
DOI: 10.1021/es404475c
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the Diffusive Flux of Persistent Organic Pollutants between Sediments and the Water Column on the Palos Verdes Shelf Superfund Site Using Polymeric Passive Samplers

Abstract: Passive samplers were deployed to the seafloor at a marine Superfund site on the Palos Verdes Shelf, California, USA, and used to determine water concentrations of persistent organic pollutants (POPs) in the surface sediments and near-bottom water. A model of Fickian diffusion across a thin water boundary layer at the sediment-water interface was used to calculate flux of contaminants due to molecular diffusion. Concentrations at four stations were used to calculate the flux of DDE, DDD, DDMU, and selected PCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 38 publications
(80 reference statements)
2
74
0
Order By: Relevance
“…Along the same lines, concentration gradients may also exist from the sediment surface vertically up into the water column, and thus the most accurate water measurement for flux calculations would be as close as possible to the sediment–water interface. However, Fernandez et al showed very minor vertical concentration gradients from the sediment surface to 24 cm above in an ocean environment. In the present study, passive samplers were placed 30 cm above the surface of the sediment in a river system with constant water movement, where we might expect this gradient to be even less important.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Along the same lines, concentration gradients may also exist from the sediment surface vertically up into the water column, and thus the most accurate water measurement for flux calculations would be as close as possible to the sediment–water interface. However, Fernandez et al showed very minor vertical concentration gradients from the sediment surface to 24 cm above in an ocean environment. In the present study, passive samplers were placed 30 cm above the surface of the sediment in a river system with constant water movement, where we might expect this gradient to be even less important.…”
Section: Resultsmentioning
confidence: 98%
“…Diffusional flux ( F s‐w ) across the sediment–water interface is assumed to be rate limited by a thin layer of stagnant water called the boundary layer (δnormalL). Calculations followed a similar method to Fernandez et al , as shown in Equation Fsw=DnormalwδnormalLtrue(CnormalwCpwtrue) …”
Section: Methodsmentioning
confidence: 99%
“…Flux was calculated following Fick’s law of diffusion (Davie-Martin et al, 2013; Eek et al, 2010; Fernandez et al, 2014): flux=DTδL(Csoilair-Citalicair) where positive values of flux indicate volatilization from soil to air (ng m −2 h −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to active sampling methods, passive samplers are deployed for weeks at a time, require no electricity, and yield time-weighted averages (Zhang et al, 2011). Previously, passive samplers have been employed to measure in situ flux of hydrophobic organic contaminants between environmental compartments such as air and water (McDonough et al, 2016; Tidwell et al, 2016) and water and sediment porewater (Fernandez et al, 2014; Liu et al, 2013a). The few passive sampling studies that have measured soil air or soil-air partitioning in situ profiled concentration gradients using polyurethane foam passive samplers near the soil surface (Wang et al, 2017; Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…LDPE passive samplers have been used to sample non-polar and semi-polar compounds in air (Paulik et al 2015; Tidwell et al 2015), water (Allan et al 2012; McDonough et al 2014), and sediment porewater (Fernandez et al 2014; Liu et al 2013). Contaminants diffuse into passive samplers, and concentrations increase until equilibrium is reached with the sampled matrix.…”
Section: Introductionmentioning
confidence: 99%